Examining learning object repositories from a knowledge management perspective - Kallonis, P.; Sampson, Demetrios (2010)
Resources and activities generated by teachers, by teacher-to-students and students-to-students interactions constitute a significant asset of considerable added-value that is worthy to be shared and possibly reused among educational communities worldwide. Moreover, these resources and activities can be considered as the "knowledge" of the educational communities, which should be managed, shared and reused effectively. Therefore, a number of international initiatives have emerged recently that recognize this potential and attempt to provide solutions for facilitating the sharing and the reuse of educational resources and activities. As a result a number of Learning Object Repositories (LORs) have been developed and are currently in operation. However, most of the existing LORs are designed more as "digital repositories of educational resources" rather than as "Knowledge Management" (KM) systems that support organizing and sharing of the educational communities' knowledge. Within this framework, in this paper we study the design and the implementation of 12 existing LORs from a KM perspective. As a result, we propose a list of essential LORs' operations that meet the current demands of web-facilitated educational communities and ultimately aim to facilitate the creation, sharing and application of "knowledge" among their members. © 2010 IEEE.